4CPS-073 Evaluation of carbapenaemic treatments and antimicrobial stewardship. (2nd March 2018) - Pablo, LTG; Maso, N El Hilali; Gloria, GS; Paula, MA; Carlos, S; Leticia, GM Maria; Nuria, PS; Montserrat, PB
Abstract : Background: Infections caused by antibiotic-resistant bacteria have increased in recent years, becoming one of the most important issues for health systems. The implementation of antimicrobial stewardship programmes is important in achieving the correct drug and dose, de-escalation and treatment duration for each patient. The goal of such programmes is to reduce the development of resistant organisms and to ensure that the use of antibiotics does not result in deleterious effects to patients. Purpose: The object of this study is to evaluate the use of carbapenem antibiotics in our hospital and to assess the results of implementing an antimicrobial stewardship programme (AS). Material and methods: During 3 months, patients treated with carbapenem antibiotics were evaluated by AS along with the first 7 days of treatment. Age, antibiotics, length of stay (LS), treatment duration (TD), immunosuppression state, sepsis, prescribing departments, diagnoses, type of treatment (directed or empirical) and in case of positive cultures, the type of bacteria were registered. Additional parameters of AS registered were: de-escalation and/or modification of TD, and the acceptance or not of the intervention. Results: AS reviewed 94 treatments with carbapenem antibiotics: mean age of patients was 78 years, (IQR 71.4–87.1), 68% with meropenem, 31% with ertapenem and 1% with imipenem/cilastatine. Mean LS was 15 days (IQR 9–33). Mean TD was 7.2 days (IQR 5–9.6). 20.2% of the patients were immunosuppressed and 71.3% were septic patients. The main prescribing departments were internal medicine 69%, intensive care unit 7.5%, general and digestive surgery and gastroenterology 5.3%. 59.6% were empirical treatments and 40.4% directed treatments. Main diagnoses were complicated cystitis (26.6%) and hospital-acquired pneumonia (11.7%). 71.3% were septic patients. Among identified microorganisms 68.2% were Gram– bacilli (GNB) with extended spectrum beta-lactamase, 15.8% Gram – fermentative bacilli and 5.3% multi-resistant GNB. 23.4% of prescriptions were evaluated as incorrect. AS proposed modifications in 37.2% of treatments and 99% of treatment recommendations were accepted. 65.7% were de-escalated and TD was modified in 48.6% of intervened treatments. Conclusion: Our results show the importance of implementing an antimicrobial stewardship programme to review antimicrobial therapy and to optimise treatments, and to standardise the use of broad-spectrum antibiotics, in order to maintain a low prevalence of resistance. No conflict of interest